Differential Expression of Intestinal Genes in Opossums with High and Low Responses to Dietary Cholesterol. (26th October 2009) - Chan, Jeannie; Kushwaha, Rampratap S.; VandeBerg, Jane F.; Gluhak-Heinrich, Jelica; VandeBerg, John L.
Abstract : High and low responding opossums ( Monodelphis domestica ) differ in their plasma very low density lipoprotein and low density lipoprotein (VLDL+LDL) cholesterol concentrations when they consume a high cholesterol diet, which is due in part to absorption of a higher percentage of dietary cholesterol in high responders. We compared the expression of a set of genes that influence cholesterol absorption in high and low responders fed a basal or a high cholesterol and low fat (HCLF) diet. Up-regulation of the ABCG5, ABCG8, and IBABP genes by the HCLF diet in high and low responders may reduce cholesterol absorption to maintain cholesterol homeostasis. Differences in expression of the phospholipase genes ( PLA2 and PLB ) and phospholipase activity were associated with differences in cholesterol absorption when opossums were fed cholesterol-enriched diets. Higher PLA2 and PLB mRNA levels and higher phospholipase activity may increase cholesterol absorption in high responders by enhancing the release of cholesterol from bile salt micelles for uptake by intestinal cells.